The Legal Protection for Patients in Medical Practice and Healthcare Services - Tandry, Novita; Muhammad Juwanda Arif; Zulfadly Siregar; Ricky Rosiwa (International Journal of Law, Social Science, and Humanities, 2024)
Legal Protection of Patients in Medical Practice and Health Services is an increasingly important issue in the context of medical law and ethics. This study aims to analyze various aspects of legal protection provided to patients based on the applicable legislation in Indonesia, specifically Law of the Republic of Indonesia Number 17 of 2023 concerning Health as the latest law, including Law Number 36 of 2009 concerning Health and Law Number 29 of 2004 concerning Medical Practice as supplements. The methodology used in this study was content analysis with a normative juridical approach, which examined legal norms and practices based on laws and gathered information from relevant and reliable secondary data sources The study results indicate that, although there are various legal provisions protecting patients, the implementation of these protections still faces challenges. This research emphasizes the importance of raising legal awareness among healthcare providers and patients themselves. It is hoped that the government and relevant institutions will conduct more intensive outreach on patient rights and enforce stricter measures against violations occurring in medical practice. Effective legal protection will not only increase public trust in the healthcare system but also enhance the overall quality of healthcare services.